Pengembangan Model Kompetensi Karyawan dalam Meningkatkan Pelayanan Program Pengembangan Masyarakat (Community development) di Departemen Social Responsibility PT. Newmont Nusa Tenggara
Empower the community is an effort to improve states and dignity levels of society which in the condition of being unable to escape from retardation. On a number of occasions, PT. Newmont Nusa Tenggara ( NNT ) often asserted, that it gives serious attention for the management of the environment and social responsibility to the community. This research is done in social responsibility department PTNNT with consideration, the social responsibility department which is a division that directly connected with the community, and became a leading to the community in mine circumference to express their opinions and complaint against PT.NNT policies and employees in social responsibility department has strategic role in running PTNNT community development program. Research methodology to be used is descriptive qualitative research method. Informants were chosen based on several criteria that has been set, and were in purposive have based on initial information obtained. The informants are managers and employees of PT. Newmont Nusa Tenggara SR (social responsibility) department and the company circle community amount to 12 people. The SR department  has strategic role in running PT. NNT community development program, however the role has not supported by  knowledge and skills mastery about fine approach method, communication , information and education a community development program itself. In other words, there should have been development competence employees the department of SR in terms of skill and knowledge . Education background with employees different kinds of work, so that knowledge and skills employees department social responsibility PT. Newmont Nusa Tenggara ( PTNNT ) where the ability and skills still need to be trained, so with the understanding of corporate social responsibility in a community development program  is not perfect yet. Competence knowledge at least from an employee of  PTNNT SR department relating to the work, PTNNT  community development programs, conformity work programs with the vision of the company a pretty reasonable. Competence skills base PTNNT SR employees includes the ability of communication, socialization, the delivery of information, approach to the community and ability affecting the public. Development model competence for employees department of  SR PTNNT based on a dictionary competence Spencer & Spencer, then adapting model competence of the learning organization. The new model of competence for employees of SR departetemen can help for  PTNNT  understand how to achieve success in employment.